Trends of Acupuncture Therapy on Depression From 2011 to 2020: A Bibliometric Analysis - Xiang, Hongchun; Li, Jing; Li, Bocun; Tan, Qian; Cai, Guowei (Frontiers in Psychology, 2021)
Objectives: The purpose of this study was to explore the current status and trends of acupuncture for depression in the last decade and provide new insights for researchers in future studies. Methods: The articles regarding acupuncture treatment for depression published between 2011 and 2020 were extracted from the Web of Science Core Collection. We used CiteSpace to analyze data on publications, countries, institutions, cited journals, cited authors, cited references, keywords, and citation bursts about acupuncture and depression. Results: A total of 1,032 publications were obtained from 2011 to 2020. We identified the most prolific journals, countries, institutions, and authors in the field of acupuncture for depression in the last decade. The most prolific country and institutions were the People's Republic of China and KyungHee University, respectively. Evidence-based Complementary and Alternative Medicine was the most prolific and cited journal. The author with the highest centrality was Zhangjin Zhang, and the author with the most publications was Park Hi-Joon. The keyword “cognitive behavioral therapy” was first for research developments with the highest citation burst. The five hot topics in acupuncture on depression were “acupuncture,” “depression,” “electro-acupuncture,” “quality of life,” and “anxiety.” Conclusions: The results from this bibliometric study provide insight into the research trends in acupuncture therapy for depression, and the current status and trends of the past decade, which may help researchers determine the current status, hotspots, and frontier trends in this field.